Effects of Goal Difficulty, Goal-Setting Method, and Expected External Evaluation on Intrinsic Motivation - Shalley, Christina E.; Oldham, Greg R.; Porac, Joseph F. (Academy of Management Journal, 1987)
The article examines the goal-setting method of corporations and its corresponding effects on the job performance of employees. A discussion is presented about employee motivation. The authors present information related to task evaluation and assessment of a goal's level of difficulty. Details are presented related to the motivational value of employee participation in goal-setting. A discussion is presented about the relationship between intrinsic motivation and cognitive evaluation theory.